2015
DOI: 10.1016/j.jcot.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of wrist joint in an 8-year-old child presenting as hamate osteitis: A rare case report

Abstract: Tuberculosis rarely involves wrist joint and is usually diagnosed in arthritic stage. We, hereby, describe a case of TB afflicting wrist joint in a young child. To our knowledge, similar presentation has never been reported. Diagnostic dilemma became more pronounced as the radiograph presented with features of osteitis of hamate instead of a classical phemister's triad, as is usually expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The lesions also healed radiologically without any sequelae. [ 11 ] Our patient had a deformity at the end of treatment. Wrist stiffness is seen frequently and has a significant functional impact.…”
Section: Discussionmentioning
confidence: 97%
“…The lesions also healed radiologically without any sequelae. [ 11 ] Our patient had a deformity at the end of treatment. Wrist stiffness is seen frequently and has a significant functional impact.…”
Section: Discussionmentioning
confidence: 97%
“…The wrist is a rare localization of tuberculosis. It represents 1% of bone and joint tuberculosis [1][2][3] . The disease generally begins in the scapho-lunar joint following haematogenic inoculation of the articular synovium in two thirds of cases, or inoculation by contiguity from tuberculosis tenosynovitis in third of cases [4,5] .…”
Section: Discussionmentioning
confidence: 99%
“…According to F. Dlimi, surgery, which is useless for a curative purpose, finds its place essentially for diagnostic or functional purposes [7] . On the other hand, A.Goel recommends debridement surgery if there is a significant destruction of the wrist [1] . P. Borman [3] and M. Komurcu [13] allow resection of the first row of carpal bones destroyed by tuberculosis for better control of infection in advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Prakash [4] reported isolated involvement of the capitate. In 2015, Sbai et al [5] and Goel et al [6] reported isolated scapholunate and hamate involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Common sites of primary osseous focus are the os capitatum or distal end of the radius [2]. Very few cases have been reported of isolated involvement of a single bone or joint in the wrist or hand [3][4][5][6][7][8]. Isolated involvement of the hamate, in particular, is even rarer.…”
Section: Introductionmentioning
confidence: 99%